Consulta Semântica Baseada em Linked Data para Ambientes de Convergência Digital (TVDi e Web) - Amaro, Manoel de Albuquerque Lira (2014)
The emergence of Digital TV brought, beyond high definition, the potential of the interactivity and metadata relative to the TV programmes, but some information provided by the broadcasts can be insufficient to the user make a decision on what he/she is going to watch. This work aims to propose a Semantic Query approach in the Interactive Digital TV environment, based on the concepts and designs of the Semantic Web, providing an advanced service of semantic query, and a way for doing metadata enrichment coming from the broadcasters, adding semantic relationships and expanding the information in a graph of data coming from the Linked Data cloud. A Web Service of Semantic Query integrated into the Knowledge-TV platform was developed to validate this proposal.